Folliculinum - Leupen, Alex (Homœopathic Links, 2014)
Alex Leupen works in the Homeopathic Doctorsʼ Centre in Utrecht, The Netherlands, since 1990. In this column he shares clinical tips.
Keywords: Folliculinum; Oral contraception; Sarcode; Fertility; Menopausal complaints